Dwelling architecture in the context of socio-economic and technological conditions of modern Kazakhstan (on the example of Almaty city) - Karlygash Tabynbayeva; Gulnar Abdrassilova (Vitruvio: International Journal of Architectural Technology and Sustainability)
The relevance of this research is highlighted by Almaty’s continuing status as a historical and cultural centre and a financially independent city, despite no longer serving as the capital of the Republic of Kazakhstan. Currently, an important issue is the formation of the “Smart City” plan in the context of modern concepts of resource conservation and environmental policy. The research aims to substantiate changes in the formation of housing architecture under the influence of socio-economic, political, and technological processes in the context of gradual historical changes in the example of Almaty, as well as to determine the priority directions of development of urban planning processes, in particular on the territory of the residential zone. The following methods of scientific research were used: abstract-logical method; comparative method; historical method; method of system analysis and synthesis. To achieve the research aims, the elements of the socio-economic development of Almaty in the context of historical, cultural, and educational centres were defined. The peculiarities of dwelling architecture from the 1920s to the present day are analysed. This research proposes priority directions for urban planning in Almaty’s residential area by analysing historical architecture influenced by socio-economic and technological factors.